How can I find Nth term for this recurrence relation
F(n) = F(n-1) + F(n-2) + F(n-1)*F(n-2)
I have to find Nth term for this recurrence relatio
There's a trick. Let G(n) = F(n) + 1
. The equation
F(n) = F(n-1) + F(n-2) + F(n-1)*F(n-2)
becomes
G(n) - 1 = G(n-1) - 1 + G(n-2) - 1 + (G(n-1) - 1) * (G(n-2) - 1)
= G(n-1) - 1 + G(n-2) - 1 + G(n-1)*G(n-2) - G(n-1) - G(n-2) + 1
= G(n-1)*G(n-2) - 1,
so adding 1
to both sides,
G(n) = G(n-1)*G(n-2).
This is the multiplicative equivalent of the familiar Fibonacci recurrence. The solution is
G(n) = G(0)^Fib(n-1) * G(1)^Fib(n),
by analogy with the theory of linear recurrences (where Fib(-1) = 1
and Fib(0) = 0
and Fib(1) = 1
), since
G(n-1)*G(n-2) = G(0)^Fib(n-2) * G(1)^Fib(n-1)
* G(0)^Fib(n-3) * G(1)^Fib(n-2)
= G(0)^Fib(n-1) * G(1)^Fib(n)
= G(n).
Hence,
F(n) = (F(0)+1)^Fib(n-1) * (F(1)+1)^Fib(n) - 1,
doing the Fib
computations via the matrix power method mod p-1
per Fermat's little theorem and the exponentiation mod p
.